The relationship between resilience, anxiety and depression among patients with mild symptoms of COVID‐19 in China: A cross‐sectional study - Zhang, Jie; Yang, Zhen; Wang, Xiao; Li, Juan; Dong, Lili; Wang, Fusheng; Li, Yifei; Wei, Ruihong; Zhang, Jingping (Journal of clinical nursing, 2020)
Aims and objectives To explore the role of resilience in anxiety and depression and to clarify their relationships among patients with mild symptoms of coronavirus disease 2019 (COVID‐19) in Wuhan, China. Background The outbreak of COVID‐19 has negatively affected some individuals, but resilience plays a decisive role in the response of individuals under pressure and can help them deal with pressure more effectively. Design The cross‐sectional descriptive correlational survey was reported in line with the STROBE guidelines. Subject and setting In total, 296 patients from FangCang Hospital in Wuhan, Hubei, China, with mild symptoms of COVID‐19 were recruited. Methods Participants were recruited through convenience sampling. The data collected included their demographic information, the Connor‐Davidson Resilience Scale and Hospital Anxiety and Depression Scale. Results A small number of patients in this study had above threshold anxiety (subthreshold anxiety and major anxiety) and depression (subthreshold depression and major depression). The mean total resilience score of the participants was slightly below the normal level of ordinary Chinese adults. Resilience was inversely associated with and was a protective factor for both anxiety and depression in our samples. Risk factors for anxiety include being female and having colleagues with COVID‐19, while a risk factor for depression was having family members with COVID‐19. Conclusions This study shows that after taking the general demographics into consideration, higher levels of resilience were associated with lower anxiety and depression among mild COVID‐19 patients in Wuhan, China. Relevance to clinical practice Health professionals, especially clinical nurses, need to be aware of the psychological status of COVID‐19 patients and promote resilience to improve their mental health.